1998
DOI: 10.1007/s001070050272
|View full text |Cite
|
Sign up to set email alerts
|

One-step tannin fixation of non-toxic protein borates wood preservatives

Abstract: Materials and methods Ten specimens for each case of Pinus sylvestris sapwood of dimensions 50 • 15 x 5 mm were treated under 15 minutes vacuum (-1 bar) and 30 minutes at atmospheric pressure with solutions of (1) boric acid (5% weight/volume) + Pinus radiata tannin extract (1% w/v) + egg albumin (1% w(v), (2) boric acid (5% w/v) + Pinus radiata tannin extract (1% w/v) + collagen (animal glue AT 400, 1% w/v), and (3) boric acid (5% w/v) + Pinus radiata tannin extract (1% w/v). Untreated specimens were also pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 3 publications
0
6
0
2
Order By: Relevance
“…Apesar de alguns estudos justificarem a alta durabilidade natural de algumas madeiras por causa de taninos presente nas mesmas (JORGE et al, 2001;MELO et al, 2010), outros citam que os taninos possuem baixa toxicidade como preservativos, mas que podem fixar biocidas pelas suas excelentes propriedades quelantes, o que significa que possuem habilidade em formar complexos com metais (LAKS;MCKAIG, 1988;THEVENON et al, 1998;BRAND et al, 2006), dificultando sua posterior lixiviação.…”
Section: Introductionunclassified
“…Apesar de alguns estudos justificarem a alta durabilidade natural de algumas madeiras por causa de taninos presente nas mesmas (JORGE et al, 2001;MELO et al, 2010), outros citam que os taninos possuem baixa toxicidade como preservativos, mas que podem fixar biocidas pelas suas excelentes propriedades quelantes, o que significa que possuem habilidade em formar complexos com metais (LAKS;MCKAIG, 1988;THEVENON et al, 1998;BRAND et al, 2006), dificultando sua posterior lixiviação.…”
Section: Introductionunclassified
“…Pizzi and Baecker [22] believed that boric acid could be used to induce the self-condensation of flavonoids and tannic acid, so that some boric acid could be stably fixed in the wood network. Thevenon et al [23] further revealed that tannins binding to proteins could better fixe boric acid or at least significantly delay its leaching. Mazela et al [24] found that 95% boric acid could be fixed by treating wood with protein preservatives and then tannic acid, and that wood treated with a mixture of boric acid and tannic acid could resist the attack of brown-rot fungi [25] .…”
Section: Research Progress On Tannins For Fixing Other Preservativesmentioning
confidence: 99%
“…Wood preservatives based on protein borates, both obtained by just mixed water solutions of protein and boric acid, as well as in the case of premanufactured protein borate salts were shown to be a good method of greatly retarding the leaching of boron from treated timber (Thevenon et al 1997(Thevenon et al , 1998aThevenon and Pizzi 2003). Thus, just premixed albumin + boric acid, premanufactured protein borate, and soy protein + boric acid all showed good preservative performance and much retarded leaching of boron.…”
Section: Biobased Wood Preservativesmentioning
confidence: 99%